PENAMBAHAN KOSAKATA DAN PENINGKATAN NILAI KEHIDUPAN PADA ANAK TUNARUNGU MELALUI MUSIKALISASI PUISI - Munika, Sinta; Nasriah, Sri (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
The student program in community services was aimed at using musical poem as the media to improve the vocabularies of deaf children and internalizing moral values into them. The methods were lecturing, demonstration, practice and performance. The performance of musical poem was to build childrenâs self confidence. The activities took four months for program preparation, implementation and then evaluation. The program was carried out for six students of Widya Mulia Special School, Pundong, Bantul, Yogyakarta. By using musical poem, it is found that the vocabularies of deaf children are improved which are shown in their written and spoken communication. Besides, the children are able to enact moral values such as religious values, confidence, autonomy, discipline and honesty. Musical poem is suitable to be implemented to deaf children based on their level of hearing ability. Therefore, the program successfully solve the deaf childrenâ problems in language learning. It is recommended for teachers in the school to implement the program for developing deaf childrenâs language skills. The children are also able to share knowledge and experiences to others for better life.Key words: musical poetry, deaf children, vocabulary, moral values